Bibliometric Analysis of Open Government: A Study on the Open Government Partnership - Rizki Erdayani; Muslim Afandi; Syed Agung Afandi (Indo-Fintech Intellectuals: Journal of Economics and Business, 2023)
This study aims to analyze the Open Government Partnership (OGP) bibliometrics. The OGP is a global effort to realize open government. In the Google Scholar database, in the span of the last decade, there have been 117 OGP articles that have been cited 486 times. From the article, there are 15 keyword clusters, 1196 total link strengths, and 428 occurrences. Open government partnership, national government, action plans, local government, and multilateral institutions are the keywords with the highest scores. Currently, 73 countries and 110 local governments have joined the OGP. To achieve open government, OGP is committed to increasing the availability of information on government activities, supporting citizen participation, applying the highest standards of professional integrity, and increasing access to new technologies. As a follow-up, OGP established ten policy areas, namely: anti-corruption and integrity, civic space, digital governance, fiscal openness, inclusion, justice, natural resources, open parliaments, public service delivery, and the right to information. OGP has also forged partnerships with leading multilateral institutions to promote and support open government